Expression of tissue factor and tissue factor pathway inhibitors during ovulation in rats: a relevance to the ovarian hyperstimulation syndrome - You Jee Jang; Hee Kyung Kim; Bum Chae Choi; Sang Jin Song; Jae Il Park; Sang Young Chun; Moon Kyoung Cho (BMC, 2021)
Abstract Background Blood coagulation has been associated with ovulation and female infertility. In this study, the expression of the tissue factor system was examined during ovulation in immature rats; the correlation between tissue factor and ovarian hyperstimulation syndrome (OHSS) was evaluated both in rats and human follicular fluids. Methods Ovaries were obtained at various times after human chorionic gonadotropin (hCG) injection to investigate the expression of tissue factor system. Expression levels of ovarian tissue factor, tissue factor pathway inhibitor (Tfpi)-1 and Tfpi-2 genes and proteins were determined by real-time quantitative polymerase chain reaction (qPCR), and Western blot and immunofluorescence analyses, respectively. Expression levels of tissue factor system were also investigated in ovaries of OHSS-induced rats and in follicular fluid of infertile women. Results The expression of tissue factor in the preovulatory follicles was stimulated by hCG, reaching a maximum at 6 h. Tissue factor was expressed in the oocytes and the preovulatory follicles. Tfpi-2 mRNA levels were mainly increased by hCG in the granulosa cells whereas the mRNA levels of Tfpi-1 were decreased by hCG. Human CG-stimulated tissue factor expression was inhibited by the progesterone receptor antagonist. The increase in Tfpi-2 expression by hCG was decreased by the proliferator-activated receptor γ (PPARγ) antagonist. Decreased expression of the tissue factor was detected in OHSS-induced rats. Interestingly, the tissue factor concentrations in the follicular fluids of women undergoing in vitro fertilization were correlated with pregnancy but not with OHSS. Conclusions Collectively, the results indicate that tissue factor and Tfpi-2 expression is stimulated during the ovulatory process in rats; moreover, a correlation exists between the levels of tissue factor and OHSS in rats but not in humans.